PEMBERDAYAAN MASYARAKAT MELALUI CORPORATE SOCIAL RESPONSIBILITY PADA UMKM DI KELUARAHAN BATU BERSURAT KECAMATAN XIII KOTO KAMPAR KABUPATEN KAMPAR - Rosmita; herman, herman; Kartius (Education and Talent Development Center of Indonesia, 2022)
Batu Bersurat Village is one of the Villages in Riau Province, precisely in District XIII Koto Kampar, Kampar Regency, where there are several companies engaged in class C excavation and plantations. Through the regulations of Riau Province Regional Regulation Number 6 of 2012 concerning Corporate Social Responsibility and Kampar Regency Regional Regulation Number 3 of 2012 concerning Corporate Social Responsibility, every company located in a certain area is obliged to empower its people in the social, economic and environmental fields. The purpose of this service is to provide knowledge, understanding and information to the community regarding the importance of community empowerment through Corporate Social Responsibility (CSR) for MSMEs and to know their rights to companies so that in the future they are able to be productive in the economic sector. This service is carried out by providing material to the participants, then a question and answer session, and ends with a discussion in the hope of finding solutions to the problems faced. The service participants were 21 people with details of 5 Kelurahan apparatus including the Lurah, and 16 people from elements of the community. It can be concluded that the implementation of community service regarding community empowerment obtained quite satisfactory results with the benefits of knowledge for the community.